THE EFFECT OF POLYVINYL PYROLYDONE (PVP), EXPLANT TYPE, AND EXPLANT PLANTING POSITION ON CALLUS GROWTH OF CIKONENG ST LARGE ORANGE (Citrus maxima (Burm.) Merr) AND SWEET ORANGE (Citrus sinensis (L.) Osbeck) - Chaidir, Liberty; Pertiwi, Rahmi (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
Cikoneng ST Orange (Citrus maxima (Burm.) Merr) is a germplasm of Sumedang area, which has been scarce for the past few years. The high percentage of browning in Cikoneng ST Orange explants is considered to be the cause of the low percentage of research success. Sweet Orange (Citrus sinensis (L.) Osbeck) is a type of orange that has been widely used as a potential orange explant in tissue culture. This study was conducted to determine the comparison of growth percentage by conducting cross-species research between Cikoneng ST Orange and Sweet Orange. The study was conducted at the Tissue Culture Laboratory of the Agrotechnology Department, Sunan Gunung Djati State Islamic University, Bandung from March to June 2017. The media used was a combination of MS media, 2 mg L-1 2.4 D, and 0.5% PVP. The explants used were leaves and leaf shoots of Cikoneng ST Orange and Sweet Orange. The planting positions of the explants included abaxial and adaxial planting positions. The study was analyzed using a descriptive method. The results showed that the administration of PVP in MS media and 2 mg L-1 2.4 D could induce callus of Sweet Orange at 3 DAI and Cikoneng ST Orange at 5 DAI. The use of leaf shoot explants and adaxial planting position produced the best friable callus up to 28 DAI. This study also found that Sweet Orange had the fastest callus growth time and a low browning percentage compared to Cikoneng ST Orange explants.